PEMBERIAN TERAPI OKSIGENASI DALAM MENGURANGI KETIDAKEFEKTIFAN POLA NAFAS PADA PASIEN CONGESTIVE HEART FAILURE (CHF) DI RUANG ICU/ICCU RSUD DR. SOEDIRMAN KEBUMEN - Mugihartadi, Mei Rika Handayani (AKPER Pemkab Purworejo, 2020)
Congestive Heart Failure is the inability of the heart to pump enough blood to carry out metabolism to meet the requirements for oxygen and nutrients in other words, it requires an abnormal increase in pressure on the heart to meet the needs of metabolism. The main problem with clients with congestive heart failure is ineffective breathing patterns. To overcome the breathing pattern is giving oxygen therapy. Objective : to determine know the application of oxygenation therapy in reducing the effectiveness of breathing patterns in patient congestive heart failure in ICU/ICCU Room DR. Soedirman Kebumen Hospital. Method : This type of research is descriptive using a case study approach. The subjects in this study were two clients who experienced congestive heart failure with criteria experiencing shortness of breath and compositional awareness. Results : showed that there were changes in breathing patterns for the better, not experiencing shortness and normal breathing frequency after being given oxygenation therapy. Conclusion : Nursing problems with ineffective breathing patterns associated with hyperventilation can be overcome with giving oxygen therapy, and increased oxygen.